Prevalence of uterine leiomyomas in the first trimester of pregnancy - Esam Abdelkareem Abdelraheem; Ahmed Mohammed Ahmed Ellethy; Amal Shohayeb Ahmed (Cairo : Esam Abdelkareem Abdelraheem, 2014)
Aim : To detect the prevalence of fibroid in the first trimester of pregnancy, detect the risk factors associated with fibroid,describe the size and location of fibroid and detection of variation in prevalence of fibroid with age material and method : the study will be designed to enroll 500 of pregnant women in the first trimester of pregnancy that comes to cairo univeresty Maternity hospital for antenatal care.transabdominal ultrasonography will be scheduled for all participants, starting from the beginning of the sixth week of gestation. Presence of leiomyomas will be defined by the Muram criteria with modification to include masses of minimum diameter of 0.5 cm or more. leiomyomata will be mapped into a uterine diagram and will be categorized by location and type
Thesis (M.Sc.) - Cairo University - Faculty of Medicine- Department of Gynecology and Obstetrics
Issued also as CD
Keywords: Frist trimester pregnancy; Ieiomyoma; Ultarasonography